Gender Discrimination Faced By African-American Women As Depicted In The Film 'Hidden Figures - Ahsani, Nizam (Journal Corner of Education, Linguistics, and Literature, 2026)
This study examines the representation of gender discrimination experienced by African-American women in the film Hidden Figures. It aims to identify the forms and impacts of workplace discrimination faced by the main character, Katherine Goble Johnson. Grounded in Black Feminist Theory as articulated by Patricia Hill Collins, this qualitative study employs descriptive analysis. Data were obtained through close textual analysis of the film, supported by relevant scholarly literature, including journals, articles, theses, and credible online sources. The findings reveal that Katherine Goble experiences multiple forms of discrimination, including gender-based exploitation, limited access to promotion, wage inequality, racial segregation, and unequal treatment within a predominantly white, male-dominated work environment. Despite these constraints, the film portrays her resilience, professional competence, and intellectual contribution, emphasizing that her value as an employee is defined by merit rather than gender or race. The study highlights how Hidden Figures reflects broader structural inequalities in the workplace and underscores the ongoing struggle for gender and racial equality.